A Case of Post-Radiotherapy Gastritis: Radiation Does Not Explain Everything - Abrunhosa-Branquinho, A (2015)
Hemorrhagic gastritis is a possible late toxicity outcome after radical radiotherapy but it is nowadays a very rare condition and most likely depends on other clinical factors. We report the case of a 77-year-old woman with a symptomatic solitary extramedullary intra-abdominal plasmacytoma and multiple gastric comorbidities, treated with external beam radiotherapy. Despite the good response to radiotherapy, the patient experienced multiple gastric bleeding a few months later, with the need of multiple treatments for its control. In this paper we will discuss in detail all aspects related to the different causes of hemorrhagic gastritis.